Kemampuan Berpikir Kritis Fisika Peserta Didik Kelas X dengan Model Brain Based Learning - Luh Devi Herliandry; Ahmad Harjono; Jannatin 'Ardhuha (Jurnal Penelitian Pendidikan IPA, 2019)
The optimal learning process, should be able to facilitate learning activities that cover both parts of the brain. This study aims to determine the effect of brain based learning model on the critical thinking ability of physics of students of class X. This research type is quasi experiment and use non-equivalent control group design with pre-test and post-test. The population in this study is all students of class X MIA SMAN 1 Gunungsari with sampling technique is purposive sampling, so obtained X MIA 3 as experiment class and X MIA 4 as control class. Data of critical thinking ability was analyzed by using t-test polled variance. Data analysis shows that tcount is 2.93 and ttable at 5% significance level of 2.0084, so tcount > ttable. Based on the result of research can be concluded that there is influence of brain based learning model to critical thinking ability physics students class X.Keywords: Brain Based Learning, Critical Thinking Ability